Serum homocysteine and physical exercise in patients with Parkinson's disease - Crispim Nascimento, Carla Manuela [UNESP]; Stella, Florindo [UNESP]; Garlipp, Celia Regina; Santos, Ruth Ferreira [UNESP]; Gobbi, Sebastiao [UNESP]; Bucken Gobbi, Lilian Teresa [UNESP] (Wiley-Blackwell, 2011)
Background: Hyperhomocysteinemia is a major risk factor for cerebral and peripheral vascular diseases, as well as cortical and hippocampal injury, including an increased risk of dementia and cognitive impairment. Elevated serum homocysteine (Hcy) concentrations are common in patients with Parkinson's disease (PD) who have been treated with levodopa; however, physical exercises can help reduce Hcy concentrations. The aim of the present study was to compare serum Hcy levels in patients with PD who partook in regular physical exercises, sedentary PD patients, and healthy controls.Methods: Sixty individuals were enrolled in the present study across three groups: (i) 17 patients who did not partake of any type of exercise; (ii) 24 PD patients who exercised regularly; and (iii) 19 healthy individuals who did not exercise regularly. All participants were evaluated by Hoehn and Yahr scale, the Unified Parkinson's Disease Rating Scale (UPDRS) and Schwab and England scale (measure daily functionality). The serum levels of Hcy were analyzed by blood samples collected of each participant. An analysis of variance and a Tukey's post hoc test were applied to compare and to verify differences between groups. Pearson's correlation and stepwise multiple regression analyses were used to consider the association between several variables.Results: Mean plasma Hcy concentrations in individuals who exercised regularly were similar to those in the healthy controls and significantly lower than those in the group that did not exercise at all (P = 0.000). In addition, patients who did not exercise were receiving significantly higher doses of levodopa than those patients who exercised regularly (P = 0.001). A positive relationship between levodopa dose and Hcy concentrations (R(2) = 0.27; P = 0.03) was observed in patients who did not exercise, but not in those patients who exercised regularly (R(2) = 0.023; P = 0.15).Conclusions: The results of the present study suggest that, even with regular levodopa therapy, Hcy concentrations in PD patients who exercise regularly are significantly lower than in patients who do not exercise and are similar Hcy concentrations in healthy controls.
Keywords: homocysteine; Parkinson's disease; physical exercise